COVID-19 AND MENTAL HEALTH: AN APPROACH FOR MANAGEMENT THROUGH AYURVEDA AND YOGA - Sarma Anil Kumar (International Journal of Applied Ayurved Research, 2021)
The COVID-19 pandemics have cast their dark shadow in almost every sphere of human life. Mental health is no more exception. COVID- 19 has affected the mental health of many in the country and all over the globe. The virulent virus has claimed over 1.79 million lives across the world to date while in India 1,48,000 people have died due to it. In India, total positive cases detected 10.2 million and out of them, 9.83 million were recovered till date (30/12/2020). The pandemic has changed the way of life for which after staying confined indoors due to the prolonged lockdown to halt the spread of the virus, adjusting to the new lifestyle in the unlocked place and that has resulted in the spectrum of illness issues ranging from depression to the fatal step- suicide. The WHO, together with partners, is providing guidance and advice during the COVID-19 pandemic. In India Ministry of health and family welfare, AYUSH ministry with several interdisciplinary AYUSH Research and Development taskforce initiating, coordinating, and monitoring against COVID-19. An approach of Ayurveda and Yoga may help to strengthen host immunity and provide an effective, accessible, and affordable means of prophylaxis of COVID-19. In this regard the Rasayana therapy, Medhya drugs as mentioned in Brihatrayee. The Satvavajaya chikitsa depicted in Sutrasthana of Charak Samhita and Yogic therapy also may play an enormous role in prevention as well as to reduce the mental disorders occurring to the suffers and common people during this time of fighting with the controlling of COVID-19 pandemic.